ANALISIS MODEL BISNIS UD LOGAM JAYA DENGAN PENDEKATAN BUSINESS MODEL CANVAS (BMC) - AHMAD AHSANUL AMAL ; Ainur Rofiq, S.Kom., SE., MM., Ph.D., CFP
The purpose of this study was to analyze the business model for the company "UD Logam Jaya" using the Business Model Canvas (BMC) approach and the UnBundling business pattern. This analysis is carried out using nine blocks in the Business Model Canvas (BMC) and Un-Bundling business patterns which consist of three types of the business core. In this study, triangulation techniques were used to test the credibility of the data by checking the data to the same source but with different techniques. Three different methods, which include interviews conducted directly and indirectly, then by conducting observations to the field, and finally the documentation. The results of this study indicate that the company "UD Logam Jaya" is suitable to use one type of core business from the business pattern of business-bundling, namely the infrastructure business model, where companies must be able to build and manage platforms or networks for high volume tasks over and over. _x000D_ _x000D_ Keywords: Business Model, Business Model Canvas (BMC), Un-Bundling Business Pattern.